Influence of phase change material volume shrinkage on the cyclic process of thermal energy storage: A visualization study. (25th February 2022) - Chen, Li; Wang, Liang; Wang, Yifei; Chen, Haisheng; Lin, Xipeng
Highlights: An acceptable and reliable image processing technique is proposed. Unconstrained melting mode, especially solidification mode is analyzed. The cooling and heating temperatures have a greater influence on heat transfer. Different solidification conditions have negligible effect on subsequent melting. Abstract: Although latent heat thermal energy storage using PCMs is widely used in the field of energy storage, a few challenges still remain. Among them, the PCM volume shrinkage during solidification has a serious impact on the current discharging process and the subsequent charging process. In this study, detailed analyses of unconstrained melting mode, especially solidification mode were studied, and an acceptable and reliable image processing technique with an uncertainty of about 0.9% was developed. In addition, the effects of cooling times (90–180 min), initial temperatures (42–60 °C), and cooling temperatures (12–30 °C), as well as the effects of heating times (30, 60 min), initial temperatures (18, 24 °C), and heating temperatures (54, 60 °C) were investigated. The results show that numerous shrinkage voids and porosity with attached air bubbles are formed inside the solidified PCM, which may reduce its effective thermal conductivity and hinder any heat transfer. The air bubbles attached to the shrinkage voids are released during the next melting process, forming several floating bubbles. The cooling and heating temperatures have a greater influence on the heat transfer rate than the initial temperature. Decrease of cooling temperature (18 °C) and increase of heating temperature (6 °C) will result in shorter solidification time (up to 46.51%) and melting time (up to 11.46%). The different solidification conditions have little effect on the subsequent melting process due to the same solidification mode.